A Comprehensive Review on Synthetic Strategy of Benzothiazole Lead and Pharmacological Importance - Bhoge ND; Mohite PB; Deshmukh VK; Magare BK (Indian Journal of Pharmacy & Drug Studies, 2023)
Background: In recent years heterocyclic compounds analogues and derivatives have attracted wide attention due to their useful biological and pharmacological properties. Benzothiazole is among the usually occurring heterocyclic nuclei in many marines as well as natural plant products. Benzothiazole is a privileged bicyclic ring system with multiple applications. Objective: To review and explore the synthetic strategy of lead and pharmacological importance of Benzthiazole Derivatives. Materials and Methods: A literature search was conducted on various database sources (like PubMed, Science Direct) with the help of a combination of different keywords: Benzothiazole, thiazole, antitumor, anti-inflammatory activity and anti-convulsant, antioxidant, anti-mutagenic, anti-diabetic, anti-hyperplasia, and antimicrobial. The search was customized by applying the appropriate filter to get the most relevant articles to meet the objective of this review. Conclusion: It is known to exhibit a wide range of biological properties including anticancer, antimicrobial, and anti-diabetic, anti-convulsant, anti-inflammatory, and anti-viral, anti-tubercular activities. A large number of therapeutic agents are synthesized with the help of benzothiazole nucleus. During recent years there have been some interesting developments in the biological activities of benzothiazole derivatives. These compounds have special significance in the field of medicinal chemistry due to their remarkable pharmacological potentialities. This review is mainly an attempt to present the research work reported in the recent scientific literature on different biological activities of benzothiazole compounds.